The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1063/1.2779287
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of energy transfer at an isolated substrate in a pulsed dc magnetron discharge

Abstract: The power density delivered by particles to an electrically isolated substrate in an asymmetric bipolar pulsed dc unbalanced magnetron has been quantified. The plasma source was operated in argon with a titanium target, and measurements were made using both a calorimeter probe and time-resolved Langmuir probe incorporated into a specially made substrate holder. The main results from the calorimeter probe show clearly that with increased pulse frequency (from dc to 350kHz) and reduced duty cycle (90%–50%), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 27 publications
2
23
0
3
Order By: Relevance
“…The thermal capacity of the probe was calculated using C P = m c P = 0.31 J/K, where m = 0.803 g is the mass of the probe and c P is the specific heat of copper, with an estimated accuracy of about ±10 %. The method used to determine the heat transfer to the substrate is based on the temporal evolution of a small calorimeter probe's temperature located at the position of the substrate [30,31].…”
Section: Power Flux Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal capacity of the probe was calculated using C P = m c P = 0.31 J/K, where m = 0.803 g is the mass of the probe and c P is the specific heat of copper, with an estimated accuracy of about ±10 %. The method used to determine the heat transfer to the substrate is based on the temporal evolution of a small calorimeter probe's temperature located at the position of the substrate [30,31].…”
Section: Power Flux Measurementsmentioning
confidence: 99%
“…The measured power flux density was P tot−15 = 38 mW/cm 2 and P tot−500 = 33 mW/cm 2 for pulse delays of 15 μs and 500 μs, respectively. The energy fluxes of particular species (ions, electrons and neutral particles) were calculated using the model described previously [7,31]. Input parameters (plasma density, electron temperature, plasma and floating potential) were taken from our Langmuir probe measurements.…”
Section: Power Flux Measurementsmentioning
confidence: 99%
“…It was observed that the fluorine content in the doped thin films is in the range of 0-7.4 at.%, which is low in comparison to the amount of fluorine incorporated into the powder targets (0-13 at.%). This can be explained by the fact that fluorine is a light element (Z = 9) and may be more readily scattered during gas phase transport through the high density plasma [19]. …”
Section: Elemental Analysismentioning
confidence: 99%
“…Čada et al measured the power density at the substrate in order to assess the interaction between the plasma and the substrate and quantify the energy balance. They concluded that pulsing the magnetron discharge provides higher energy transfer to the growing film this, in turn, produces denser film structures [19].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the simplicity of calorimetric probes they can easily be integrated into a substrate holder as performed by Ball [45] or Cada et al [49] (see Figs. 6.4f and 6.5a).…”
Section: Probe Layoutsmentioning
confidence: 99%